Determinants of intrapreneurial behavior: The effects of psychological and organisational factors. - Ahmad, Noor Hazlina (Universiti Sains Malaysia, 2012)

(untitled)
The aim of this paper is to investigate the psychological and organisational factors that can be crafted to promote intrapreneurial behaviour among Malaysian workforce which could subsequently enhance their overall performance. This study specifically examines the effects of psychological factors (Le., locus of control, propensity to take risk, and need for achievement as well as the organisational factors (i.e., management support, work discretion, reward and reinforcement, organisational boundaries and time availability) on intrapreneurial behaviour. Following that, the effect of intrapreneurial behaviour on job performance is also tested. Multiple regression is utilised to test the hypothesized relationships. The findings unearthed that all paths are significant except for the effect of time availability on intrapreneurial behaviour. Overall, this study offers valuable insights into the psychological factors as well as factors within an organisation that could instigate intrapreneurial culture among Malaysian workforce.